Forming method for improving density of ceramic fiber reinforced ceramic-based composite material
Through the combination of the precision and curing process of the front -drive body and the high -temperature pressure sintering process, the problem of low density density of silicon nitrite composite material in the existing technologies has achieved low density and excellent mechanical properties of the material. It meets the high temperature -resistant transmission requirements of Gaoma -counting aircraft.
Patent Information
- Application Number
- CN202411658716.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-11-20
AI Technical Summary
In the prior art, the silicon nitride fiber reinforced silicon nitride composite materials have low density and complex processes, resulting in poor material performance and difficult to meet the high temperature wave-transmitting requirements of high-Mach number aircraft.
By combining the precision and solidification process of the front drive body with the high -temperature pressure sintering process, the optimized design substrate material is used to regulate the process parameters to improve the density and the uniformity of the substrate of the composite material.
The density of composite materials was achieved to about 70%, reducing the internal defects of the material, improving mechanical properties and heat resistance, and meeting the needs of high -performance high -temperature resistance to high temperature -resistant transmittance materials.
Smart Images

Figure CN119371221A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of composite material preparation, in particular to a molding method for improving the density of ceramic fiber reinforced ceramic matrix composite material. Background Art
[0002] With the development of various new aircraft towards higher Mach flight speeds and longer flight distances, higher requirements are placed on a series of properties such as high temperature resistance, wave transmission, and load-bearing in their wave-transmitting and heat-proof components. They are required to withstand greater loads and aerodynamic thermal shocks in more severe working environments, and the working temperature can reach above 1400°C, and meet the requirements of high wave transmission characteristics. Ceramic materials are often the preferred materials for high-temperature resistant and wave-transmitting components of aircraft in the aerospace field because of their good high temperature resistance, heat protection, high strength and excellent electrical properties. Among wave-transmitting materials, traditional quartz ceramic materials have a low operating temperature, and the long-term non-ablation temperature does not exceed 1000°C, which cannot meet the high Mach number requirements of high-speed aircraft. The electrical properties of alumina ceramics, such as dielectric constant and dielectric loss, are poor, and cannot meet the requirements of wave transmission of components in high temperature environments. Silicon nitride ceramics have excellent high temperature resistance and electrical properties, but the inherent brittleness and other shortcomings of ceramic materials limit their reliability.
[0003] Further research has found that ceramic fiber reinforced ceramic matrix composites have greatly improved material reliability due to the fiber reinforcement and toughening effect, and stand out in the selection of high-temperature resistant and wave-transparent components. Among them, silicon nitride fiber reinforced silicon nitride composites have become ideal high-temperature resistant and wave-transparent ceramic materials for high-speed aircraft due to their excellent dielectric properties, outstanding high-temperature resistance and high mechanical reliability.
[0004] Silicon nitride fiber reinforced silicon nitride composite materials mainly refer to ceramic composite materials with silicon nitride fibers as reinforcing fibers and silicon nitride as the matrix. Further research on silicon nitride fibers found that silicon nitride fibers have excellent thermal shock resistance and room temperature / high temperature mechanical properties, and their use temperature in an inert atmosphere can reach above 1400°C. The electrical properties such as dielectric constant and dielectric loss are moderate, showing excellent load-bearing and wave-transmitting performance. Therefore, silicon nitride composite materials prepared by silicon nitride matrix composite have good high-temperature mechanical properties, stable electrical properties and anti-ablation properties, and are ideal materials for high-temperature resistant and wave-transmitting components of future aircraft.
[0005] At present, the preparation of silicon nitride fiber reinforced silicon nitride composite materials mainly adopts the precursor impregnation pyrolysis (PIP) process. This process is to weave silicon nitride fibers into fiber preforms, and then fully immerse the preforms in polysilazane organic precursors. The preforms impregnated with the precursors are cross-linked and cured at a certain temperature, and then the preforms with the precursor solidified are placed in a high-temperature sintering furnace for high-temperature pyrolysis reaction treatment. The organic precursors are converted into ceramic matrix through pyrolysis reaction, and then the preforms are densified. Through repeated immersion, curing and pyrolysis steps of ceramic precursors, silicon nitride fiber reinforced silicon nitride composite materials are finally prepared. For example, CN112010654A, CN104261850A, CN115636681A, etc.
[0006] The silicon nitride precursor (i.e., polysilazane) used in the PIP process is generally viscous and has poor fluidity, which results in uneven distribution of the precursor inside the fiber preform after it is immersed in the preform and solidified. What is more, the ceramic yield of the precursor solidified material is not high (generally less than 70%), and small molecular gases will be released during the cracking process. The resulting pores will further reduce the density of the composite material, resulting in a single poor effect on the overall density improvement of the composite material. At present, due to the limitations of the process and precursors, this type of composite material can only be prepared by multiple impregnation and curing of the composite precursor. However, even so, the effect of improving the density of the composite material and the uniformity of the matrix is still limited, and the porosity of the final product can still be as high as 45% or more. Multiple rounds of cracking and composite treatment will also reduce the strength of the fiber preform. In this case, the mechanical properties, heat resistance and dielectric properties of the composite material will be greatly reduced, so that it is impossible to obtain an ideal high-temperature resistant and wave-transmitting composite material.
[0007] In order to solve the technical problems in the preparation of silicon nitride fiber reinforced silicon nitride composites by the PIP process, multiple rounds of high-temperature cracking process aggravate fiber damage, low yield of polysilazane ceramics, poor internal uniformity of the matrix after cracking, resulting in low density and poor performance of the composite materials, it is necessary to innovate the composite process of silicon nitride fiber reinforced silicon nitride composites. Summary of the invention
[0008] In order to solve the technical problems existing in the prior art, the present invention provides a molding method for improving the density of ceramic fiber reinforced ceramic matrix composite materials. The present invention combines the precursor impregnation and curing process with the high-temperature pressure sintering process, and selects an optimized designed matrix to maximize the solution to the problem of uneven matrix distribution formed by the cracking of polysilazane in the existing process, reduce the internal defects of the material, and increase the density of the composite material to about 70%.
[0009] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0010] In one aspect, the present invention provides a molding method for improving the density of a ceramic fiber reinforced ceramic matrix composite material, comprising:
[0011] (1) Preparation of silicon nitride fiber preform: placing a preform formed by weaving silicon nitride fibers into a mold required for impregnation; the weaving is three-dimensional weaving, and the volume content of the fibers in the fiber preform is 35-50%;
[0012] (2) Immersing the prepared polysilazane precursor mixture into the mold in step (1) by vacuum suction, ensuring that the liquid level covers the surface of the fiber preform;
[0013] The precursor mixture is composed of the following components in mass percentage: 60-90wt% of polysilazane; 10-40wt% of powder; the powder is a mixture of silicon nitride powder and yttrium oxide powder, wherein the amount of yttrium oxide powder is 4-6wt% of the total mass of the powder; the particle size of the silicon nitride powder is 100-500nm, and the particle size of the yttrium oxide powder is 50-200nm;
[0014] (3) Then, the mold in step (2) is placed in a hot pressing sintering furnace, the temperature is raised to 180-200° C., and the temperature is kept for 2-4 hours under a nitrogen atmosphere to ensure that the polysilazane in the precursor mixture is completely cured;
[0015] (4) Then, the mold in the hot pressing sintering furnace in step (3) is pressurized to an initial pressure of 0.5 MPa to ensure that the pressure head in the furnace is in contact with the sample. After 2 hours, the temperature is further increased to 600-700°C and kept at this temperature for 2-4 hours;
[0016] (5) The hot pressing sintering furnace in step (4) is then pressurized to ensure that the pressure applied to the mold reaches 30-60 MPa;
[0017] (6) The hot pressing sintering furnace in step (5) is then heated to 1200-1400°C after 2-3 hours, and kept at this temperature for 2-6 hours while maintaining the pressure. After the end of the heat preservation, the temperature is lowered to 1000°C and the pressure is released to normal pressure within 10 minutes;
[0018] (7) The hot pressing sintering furnace in step (6) is then cooled to below 100° C., the furnace is opened and samples are taken to obtain a silicon nitride fiber reinforced silicon nitride composite material, thus completing the entire composite process.
[0019] On the other hand, the present invention also provides a ceramic fiber reinforced ceramic matrix composite material prepared by the above method.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] The present invention proposes a new densification molding composite process for silicon nitride fiber reinforced silicon nitride composite materials. The process innovatively combines the precursor impregnation and curing process with the high-temperature pressure sintering process, selects an optimized designed matrix, and regulates the process parameters of different composite stages to maximize the solution to the problem of uneven matrix distribution formed by the cracking of polysilazane in the existing process, reduce internal defects in the material, and increase the density of the composite material to about 70%. The number of composite times is reduced to reduce the degree of damage to the fiber, so that the fiber can exert a better reinforcement and toughening effect, effectively improve the tensile and bending mechanical properties of the composite material, and finally obtain a high-performance silicon nitride fiber reinforced silicon nitride composite material.
[0022] On the basis of reducing the number of composite times, the present invention further improves the density of the composite material and the uniform distribution of the matrix by combining the precursor impregnation and curing process with the high-temperature pressure sintering process, thereby obtaining a high-performance silicon nitride fiber reinforced silicon nitride high-temperature resistant and wave-transmitting composite material.
[0023] The present invention prepares the silicon nitride fiber preform impregnated with the polysilazane precursor mixture by placing it into a high-temperature hot-pressing sintering furnace for curing-cracking integrated sintering composite preparation, and the fiber reinforcement and the matrix can be composited through a single hot-pressing sintering process. Compared with the traditional PIP process, it avoids the repeated impregnation process of the precursor, reduces the damage to the silicon nitride fiber caused by multiple rounds of high-temperature cracking, greatly shortens the production cycle, greatly reduces the production cost, and is more conducive to industrial production.
[0024] The impregnated material used in the present invention is a composite impregnated phase formed by mixing a polysilazane precursor, a silicon nitride powder matrix, and an yttrium oxide sintering aid. Compared with the low yield of a single polysilazane ceramic, there will be a large amount of mass loss during the cracking and compounding process, so that a large number of pore defects will be generated after a single compounding. Adding silicon nitride powder to the impregnated material can greatly improve the impregnation efficiency and the weight gain of the impregnation, reduce the pore content generated in the cracking of the precursor, and effectively improve the final density of the composite material. Compared with the single polysilazane precursor impregnation compounding, the impregnation efficiency is increased by more than 50% by impregnation with a mixture of polysilazane and silicon nitride powder, and the final density of the material is increased by 20~50%, and in the presence of yttrium oxide sintering aid, the sintering temperature of the silicon nitride powder can be significantly reduced, so that at a relatively low temperature in the range of 1200~1400°C, while ensuring that the silicon nitride fiber is not damaged, a sintered dense silicon nitride matrix is obtained.
[0025] The sintering process proposed in the present invention is an innovatively designed process. Compared with the traditional hot pressing sintering process, the process link proposed in the present invention has obvious innovation. In a hot pressing sintering furnace, the precursor is first cured and formed at 180~200℃, and then directly heated to 600~700℃ in the furnace. At this temperature, the polysilazane precursor solidified material will begin to crack and form a powdered silicon nitride matrix. At this time, a pressurization operation is performed. Since the fiber preform is an integral structure, it can still ensure its own integrity under high pressure, and the powdered matrix formed by the initial cracking will produce a certain fluidity under high pressure, so that the powdered matrix will be evenly and fully diffused into the complete silicon nitride fiber preform, reducing the number and size of pore defects inside the composite material, and maximizing the solution to the problem of uneven matrix distribution formed by the cracking of polysilazane in the existing PIP process. When the temperature continues to rise to 1200~1400℃, under the action of pressure, the product after curing of polysilazane continues to decompose into powder and flow evenly into the interior of the preform, and under the action of high temperature, high pressure and yttrium oxide sintering aid, the silicon nitride powder will form liquid phase sintering, which promotes the densification sintering of silicon nitride, thereby completing the composite process. And the sintering temperature is lower than 1400℃, which will not affect the state and performance of the silicon nitride fiber itself. Finally, under the promotion of the new preparation process proposed by the present invention, the internal uniformity and density of the composite material are effectively improved, and the comprehensive properties of the composite material such as mechanical properties and heat resistance are greatly improved, and finally the smooth preparation of high-performance silicon nitride fiber reinforced silicon nitride high temperature resistant and wave-transparent composite materials is achieved. This process is an innovative design based on this type of material to address the technical difficulties of low density, poor internal uniformity and low strength of composite materials in the PIP process.
[0026] At the same time, the new composite method in the composite material preparation process involved in the present invention has a relatively simple process, is easy to operate and easy to master, and has no stringent requirements on equipment. The present invention greatly improves the feasibility of industrial preparation of silicon nitride fiber reinforced silicon nitride composite materials, effectively improves the density, force, heat and other comprehensive properties of the composite materials, and has a promoting significance for the subsequent development of silicon nitride fiber reinforced silicon nitride composite materials and high temperature resistant and wave-transparent materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is a CT detection image after the flat plate component is composited in Example 1 of the present invention. DETAILED DESCRIPTION
[0028] In order to make the technical problems to be solved, technical solutions and advantages of the present invention more clear, a detailed description will be given below with reference to the accompanying drawings and specific embodiments.
[0029] In the present invention, the materials used can be obtained from commercial sources unless otherwise specified.
[0030] The present invention provides a molding method for improving the density of ceramic fiber reinforced ceramic matrix composite materials, and specific embodiments are as follows.
[0031] Example 1
[0032] A molding method for improving the density of a ceramic fiber reinforced ceramic matrix composite material, comprising:
[0033] (1) Processing silicon nitride fibers into a fiber preform with a fiber volume content of 43% by three-dimensional weaving;
[0034] (2) Weighing 900 g of polysilazane, 95 g of silicon nitride powder and 5 g of yttrium oxide powder, and mixing them thoroughly by ball milling to prepare an impregnation mixture of polysilazane precursor (90 wt%), silicon nitride powder and yttrium oxide powder; then, the prepared mixed impregnation material is introduced into the mold containing the fiber preform in step (1) by vacuum suction, and the liquid level is ensured to be above the upper surface of the fiber preform;
[0035] (3) Then, the mold containing the silicon nitride fiber preform impregnated with the precursor mixture obtained in step (2) is placed in a hot pressing sintering furnace, the temperature is raised to 180° C., and the temperature is kept for 4 hours under a nitrogen atmosphere to ensure that the polysilazane in the precursor mixture is completely cured;
[0036] (4) Then, the mold in the hot pressing sintering furnace in step (3) was pressurized to give an initial pressure of 0.5 MPa to ensure that the pressing head was in contact with the sample. After 2 hours, the temperature was further increased to 600°C and kept at this temperature for 3 hours.
[0037] (5) Then, the mold in the hot pressing sintering furnace in step (4) is pressurized to 30 MPa;
[0038] (6) The hot pressing sintering furnace in step (5) is then heated to 1400°C in 2 hours, kept at this temperature for 5 hours, and maintained at a pressure of 30 MPa. The temperature is then lowered to 1000°C and the pressure is released to normal pressure within 10 minutes.
[0039] (7) Then, the hot pressing sintering furnace in step (6) was cooled to 80°C and the furnace was opened for sampling.
[0040] Example 2
[0041] A molding method for improving the density of a ceramic fiber reinforced ceramic matrix composite material, comprising:
[0042] (1) Processing silicon nitride fibers into a fiber preform with a fiber volume content of 43% by three-dimensional weaving;
[0043] (2) Weighing 700 g of polysilazane, 285 g of silicon nitride powder and 15 g of yttrium oxide powder, and mixing them thoroughly by ball milling to prepare an impregnation mixture of polysilazane precursor (70 wt%), silicon nitride powder and yttrium oxide powder; then, the prepared mixed impregnation material is introduced into the mold containing the fiber preform in step (1) by vacuum suction, and the liquid level is ensured to be above the upper surface of the fiber preform;
[0044] (3) Then, the mold containing the silicon nitride fiber preform impregnated with the precursor mixture obtained in step (2) is placed in a hot pressing sintering furnace, the temperature is raised to 200° C., and the temperature is kept for 3 hours under a nitrogen atmosphere to ensure that the polysilazane in the precursor mixture is completely cured;
[0045] (4) Then, the mold in the hot pressing sintering furnace in step (3) was pressurized to give an initial pressure of 0.5 MPa to ensure that the pressing head was in contact with the sample. After 2 hours, the temperature was further increased to 700°C and kept at this temperature for 4 hours.
[0046] (5) Then, the mold in the hot pressing sintering furnace in step (4) is pressurized to 60 MPa;
[0047] (6) The hot pressing sintering furnace in step (5) is then heated to 1300°C in 2 hours, kept at this temperature for 6 hours, and maintained at a pressure of 60 MPa. The temperature is then lowered to 1000°C and the pressure is released to normal pressure within 10 minutes.
[0048] (7) The hot pressing sintering furnace in step (6) is then cooled to 90°C and the furnace is opened for sampling.
[0049] Example 3
[0050] A molding method for improving the density of a ceramic fiber reinforced ceramic matrix composite material, comprising:
[0051] (1) Processing silicon nitride fibers into a fiber preform with a fiber volume content of 43% by three-dimensional weaving;
[0052] (2) Weighing 800 g of polysilazane, 190 g of silicon nitride powder and 10 g of yttrium oxide powder, and mixing them thoroughly by ball milling to prepare an impregnation mixture of polysilazane precursor (80 wt%), silicon nitride powder and yttrium oxide powder; then vacuuming the prepared mixed impregnation material into the mold containing the fiber preform in step (1) to ensure that the liquid level covers the upper surface of the fiber preform;
[0053] (3) Then, the mold containing the silicon nitride fiber preform impregnated with the precursor mixture obtained in step (2) is placed in a hot pressing sintering furnace, the temperature is raised to 190° C., and the heat is maintained for 2 hours under a nitrogen atmosphere to ensure that the polysilazane in the precursor mixture is completely cured;
[0054] (4) Then, the mold in the hot pressing sintering furnace in step (3) was pressurized to give an initial pressure of 0.5 MPa to ensure that the pressing head was in contact with the sample. After 2 hours, the temperature was further increased to 650°C and kept at this temperature for 2 hours;
[0055] (5) Subsequently, the mold in the hot pressing sintering furnace in step (4) is pressurized to 50 MPa;
[0056] (6) The hot pressing sintering furnace in step (5) is then heated to 1200°C in 2 hours, kept at this temperature for 4 hours, and maintained at a pressure of 50 MPa. The temperature is then lowered to 1000°C and the pressure is released to normal pressure within 10 minutes.
[0057] (7) Then, the hot pressing sintering furnace in step (6) was cooled to 80°C and the furnace was opened for sampling.
[0058] In order to further illustrate the beneficial effects of the present invention, the following comparative example was constructed.
[0059] Comparative Example 1
[0060] A method for preparing a ceramic fiber reinforced ceramic matrix composite material, comprising:
[0061] (1) Processing silicon nitride fibers into a fiber preform with a fiber volume content of 43% by three-dimensional weaving;
[0062] (2) impregnating the fiber preform with the polysilazane precursor by vacuum inhalation impregnation, raising the temperature of the mold containing the fiber preform fully impregnated with polysilazane to 180° C., and keeping the temperature for 4 hours under a nitrogen atmosphere to ensure that the precursor is completely cured;
[0063] (3) The fiber preform with the polysilazane cured product in step (2) is then taken out, placed in a high-temperature cracking furnace, treated at 1400° C. in an ammonia atmosphere for 5 hours, and taken out after cooling. At this point, a complete polysilazane impregnation-curing-cracking process is completed;
[0064] (4) Steps (2) and (3) are then repeated. After the fourth compounding process is completed, the compounding weight gain is 3.7 wt%, and the compounding is completed.
[0065] The raw materials and cracking process temperature parameters for preparing the silicon nitride fiber reinforced silicon nitride composite material used in Comparative Example 1 are similar to those in Example 1, while Comparative Example 1 adopts the traditional PIP composite process, and the impregnated material is a single polysilazane precursor, and the number of composites is increased by 3 times compared with Example 1.
[0066] Comparative Example 2
[0067] A method for preparing a ceramic fiber reinforced ceramic matrix composite material, comprising:
[0068] (1) Processing silicon nitride fibers into a fiber preform with a fiber volume content of 43% by three-dimensional weaving;
[0069] (2) impregnating the fiber preform with the polysilazane precursor by vacuum inhalation impregnation, raising the temperature of the mold containing the fiber preform fully impregnated with polysilazane to 200° C., and keeping the temperature for 3 hours under a nitrogen atmosphere to ensure that the precursor is completely cured;
[0070] (3) The fiber preform with the polysilazane cured product in step (2) is then taken out, placed in a high-temperature cracking furnace, treated at 1300° C. in an ammonia atmosphere for 6 hours, and taken out after cooling. At this point, a complete polysilazane impregnation-curing-cracking process is completed;
[0071] (4) Steps (2) and (3) are then repeated. After the fifth compounding process is completed, the compounding weight gain is 1.9 wt%, and the compounding is completed.
[0072] The raw materials and cracking process temperature parameters for preparing silicon nitride fiber reinforced silicon nitride composite materials used in Comparative Example 2 are similar to those in Example 2, while Comparative Example 2 adopts the traditional PIP composite process, and the impregnated material is a single polysilazane precursor, and the number of composites is increased by 4 times compared with Example 2.
[0073] Comparative Example 3
[0074] A method for preparing a ceramic fiber reinforced ceramic matrix composite material, comprising:
[0075] (1) Processing silicon nitride fibers into a fiber preform with a fiber volume content of 43% by three-dimensional weaving;
[0076] (2) impregnating the fiber preform with the polysilazane precursor by vacuum inhalation impregnation, raising the temperature of the mold containing the fiber preform fully impregnated with polysilazane to 190° C., and keeping the temperature for 2 hours under a nitrogen atmosphere to ensure that the precursor is completely cured;
[0077] (3) The fiber preform with the polysilazane cured product in step (2) is then taken out, placed in a high-temperature cracking furnace, treated at 1200° C. in an ammonia atmosphere for 4 hours, and taken out after cooling. At this time, a complete polysilazane impregnation-curing-cracking process is completed;
[0078] (4) Steps (2) and (3) are then repeated. After the fourth compounding process is completed, the compounding weight gain is 3.1 wt%, and the compounding is completed.
[0079] The raw materials and cracking process temperature parameters for preparing the silicon nitride fiber reinforced silicon nitride composite material used in Comparative Example 3 are similar to those in Example 3, while Comparative Example 3 adopts the traditional PIP composite process, and the impregnated material is a single polysilazane precursor, and the number of composites is increased by 3 times compared with Example 3.
[0080] Comparative Example 4
[0081] A method for preparing a ceramic fiber reinforced ceramic matrix composite material, comprising:
[0082] (1)-(3) Same as Example 1;
[0083] (4) The fiber preform with the polysilazane cured product in step (3) is then taken out, placed in a high-temperature cracking furnace, treated in an ammonia atmosphere at 1400° C. for 5 hours, and taken out after cooling. At this time, a complete polysilazane impregnation-curing-cracking process is completed, and the composite is completed.
[0084] Comparative Example 5
[0085] The precursor mixture of this comparative example includes 500 g of polysilazane, 475 g of silicon nitride powder and 25 g of yttrium oxide powder, and the other conditions are the same as those of Example 1.
[0086] Comparative Example 6
[0087] In the precursor mixture of this comparative example, silicon nitride powder was omitted, and other conditions were the same as those of Example 1.
[0088] Comparative Example 7
[0089] In the precursor mixture of this comparative example, yttrium oxide powder was omitted, and the other conditions were the same as those of Example 1.
[0090] Comparative Example 8
[0091] A method for preparing a ceramic fiber reinforced ceramic matrix composite material, comprising:
[0092] (1)-(3) Same as Example 1;
[0093] (4) Subsequently, the mold in the hot pressing sintering furnace in step (3) is pressurized to 30 MPa;
[0094] (5) The hot pressing sintering furnace in step (4) is then heated to 1400°C in 2 hours, kept at this temperature for 5 hours, and maintained at a pressure of 40 MPa. The temperature is then lowered to 1000°C and the pressure is released to normal pressure within 10 minutes.
[0095] (6) The hot pressing sintering furnace in step (5) is then cooled to 80°C and the furnace is opened for sampling.
[0096] Comparative Example 9
[0097] A method for preparing a ceramic fiber reinforced ceramic matrix composite material, comprising:
[0098] (1)-(4) Same as Example 1;
[0099] (5) The hot pressing sintering furnace in step (4) is then heated to 1400° C. in 2 hours, kept at this temperature for 5 hours, and then depressurized to normal pressure after the end of the heat preservation;
[0100] (6) The hot pressing sintering furnace in step (5) is then cooled to 80°C and the furnace is opened for sampling.
[0101] The inventors conducted performance tests on the composite materials prepared in the above examples and comparative examples. The test standards were based on "GJB873-2015 Test Method for Room-Temperature Tensile Properties of Continuous Fiber-Reinforced Advanced Ceramic Composites" and "ASTM C1341-2006 Standard Test Method for Flexural Properties of Continuous Fiber-Reinforced Advanced Ceramic Composites". The results are shown in Figure 1 and Table 1-2.
[0102] Table 1
[0103]
[0104] As shown in Table 1, the density of the composite material prepared by the method of the present invention is increased by 13-22% compared with the conventional impregnation-cracking method, and the tensile strength and flexural strength are increased by 24.6-57.1% and 38.1-69.8% respectively. The composite material obtained by the method of the present invention is tested by CT ( Figure 1 ), showing that the internal structure of the material is relatively uniform and dense. The composite materials obtained in Comparative Examples 1-3 have an uneven internal structure and poor density compared to Examples 1-3.
[0105] The present invention prepares the composite by placing the silicon nitride fiber preform impregnated with the precursor mixture into a high-temperature hot-pressing sintering furnace for curing-cracking integrated sintering. The fiber reinforcement phase and the matrix can be composited through a single sintering process. Compared with the traditional PIP process, the material production cycle is greatly shortened, the production cost is reduced, and the reduction in the number of material composites reduces the damage to the fiber reinforcement phase. Under the combined effect, the mechanical properties such as tensile strength and bending strength of the composite material are greatly improved, and the preparation of high-performance silicon nitride fiber-reinforced silicon nitride high-temperature resistant and wave-transmitting composite materials is realized, which is of great significance for the subsequent development of high-temperature resistant and wave-transmitting functional ceramic materials.
[0106] Table 2
[0107]
[0108] As can be seen from Table 2, in Comparative Example 4, only silicon nitride powder is added to improve the efficiency of single impregnation composite, but it has little effect on improving the density, tensile strength and flexural strength of the composite material. In Comparative Example 5, there is too much powder and the viscosity of the precursor mixture is relatively high, resulting in a small amount of matrix immersed in the preform during the impregnation process, resulting in a poor single-composite densification effect, and the viscosity is too high, resulting in a very uneven distribution of the matrix inside the preform. In Comparative Example 6, without adding silicon nitride powder, the composite material obtained by single composite has a low degree of densification and poor mechanical properties. In Comparative Example 7, the sintering aid is omitted, and the silicon nitride powder has a low degree of densification at low temperature, and the density is slightly lower than that of Example 1, and the flexural strength is also significantly reduced. In Comparative Example 8, the prepolymer remains in a solid state after solidification and has high brittleness. When it is not cracked into powder, high pressure is directly applied, which will cause cracking. During the cracking process, the fiber preform will be pulled apart, resulting in a sharp drop in tensile strength. However, since the internal matrix content does not change much, the density is acceptable and has a certain bending strength, but the uniformity is very poor. In Comparative Example 9, the high pressure process is omitted. At this time, the pressure has little help on the fluidity of the powder after cracking, resulting in low matrix composite efficiency and low internal uneven density.
[0109] In summary, the present invention combines the precursor impregnation and curing process with the high-temperature pressure sintering process, selects an optimized impregnation matrix material, and adjusts the process parameters of different composite stages according to the characteristics of the matrix material, thereby maximally solving the problem of uneven matrix distribution formed by the cracking of polysilazane in the existing process, reducing the internal defects of the material, and greatly improving the unevenness and density of the composite material.
[0110] The above is a preferred embodiment of the present invention. For ordinary technicians in this technical field, making several improvements and modifications without departing from the principles of the present invention should also be regarded as within the protection scope of the present invention.
Claims
1. A molding method for improving the density of ceramic fiber reinforced ceramic matrix composite materials, characterized in that: include: (1) placing a fiber preform formed by weaving silicon nitride fibers into a mold required for impregnation; (2) Adding the precursor mixture into the mold in step (1) to ensure that the liquid level covers the upper surface of the fiber preform; The precursor mixture is composed of the following components in percentage by weight: 60-90 wt% of polysilazane; 10-40% of powder; the powder is a mixture of silicon nitride powder and yttrium oxide powder; wherein the amount of yttrium oxide powder is 4-6 wt% of the total weight of the powder; (3) Then, the mold in step (2) is placed in a hot pressing sintering furnace, and the temperature is increased to completely solidify the precursor mixture; (4) The mold in the hot pressing sintering furnace of step (3) is then pressurized at a pressure of 0.5 MPa for 2 hours, and then the temperature is continuously raised to 600-700°C and kept at this temperature for 2-4 hours; (5) The hot pressing sintering furnace in step (4) is then pressurized to ensure that the pressure applied to the mold reaches 30-60 MPa; (6) The hot pressing sintering furnace in step (5) is then heated to 1200-1400° C. within 2-3 hours, and the pressure is maintained for 2-6 hours. The temperature is then reduced to 1000° C. and the pressure is released to normal pressure within 10 minutes. (7) The hot pressing sintering furnace in step (6) is then cooled to below 100° C., the furnace is opened and samples are taken to obtain a silicon nitride fiber reinforced silicon nitride composite material.
2. The method according to claim 1, characterized in that In the step (1), the weaving is three-dimensional weaving, and the volume content of the fiber in the fiber preform is 35-50%.
3. The method according to claim 2, characterized in that The particle size of the silicon nitride powder is 100-500 nm, and the particle size of the yttrium oxide powder is 50-200 nm.
4. The method according to claim 1, characterized in that: In the step (3), the temperature is 180-200° C. and the temperature is kept in a nitrogen atmosphere for 2-4 hours.
5. A ceramic fiber reinforced ceramic matrix composite material prepared by the method according to any one of claims 1 to 4.
Citation Information
Patent Citations
High-temperature-resistant wave-transparent silicon nitride fiber-reinforced composite material and preparation method thereof
CN104261850A
Fiber-reinforced silicon nitride composite material and preparation method thereof
CN112010654A
Anti-falling ceramic material and preparation method thereof
CN113929469A
High-density ceramic-based composite material and preparation method thereof
CN113979784A
Nitride fiber reinforced silicon nitride composite material and preparation method and application thereof
CN115636681A